2006
DOI: 10.1111/j.1440-1711.2006.01463.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential segregation of protective immunity by encoded antigen in DNA vaccine against pseudorabies virus

Abstract: Summary A murine model immunized with plasmid DNA vaccine expressing three glycoproteins pCIgB, pCIgC and pCIgD were used to examine the relative potency of major glycoproteins as well as the contribution of immunological parameters in providing protective immunity against the pseudorabies virus (PrV). Among the three glycoprotein-encoded plasmid DNA vaccines, pCIgB produced the strongest response of PrV-specific IgG in the sera. pCIgB and pCIgD also induced a contrast pattern of immunity that was biased to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 33 publications
(67 reference statements)
5
16
1
Order By: Relevance
“…The circles on the graph represent the individual IgG levels and the height of the bar shows the average of each group. P-values in graphs were calculated using the Student's t-test. previous report that illustrated the substantial role that gB plays as a dominant immunogen in the effective protection of a PrV DNA vaccination (Yoon et al, 2006). In addition, the strongest responses of Th1-type CD4 + T cells observed in this study were noted in mice that received gBexpressing plasmid DNA, which provided effective protection against a virulent viral infection (Yoon et al, 2006).…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…The circles on the graph represent the individual IgG levels and the height of the bar shows the average of each group. P-values in graphs were calculated using the Student's t-test. previous report that illustrated the substantial role that gB plays as a dominant immunogen in the effective protection of a PrV DNA vaccination (Yoon et al, 2006). In addition, the strongest responses of Th1-type CD4 + T cells observed in this study were noted in mice that received gBexpressing plasmid DNA, which provided effective protection against a virulent viral infection (Yoon et al, 2006).…”
Section: Discussionsupporting
confidence: 60%
“…There is increasing evidence that cell-mediated immunity is important in effective induction of protective immunity against herpesviruses Fischer et al, 2000;Eo et al, 2001;van Rooil et al, 2004;La et al, 2005), and the significance of Th1-type CD4 + effector T cells in protective immunity has been demonstrated with a PrV-infected murine model Yoon et al, 2006). In our study, the replication-incompetent adenoviruses expressing gB showed Th1-biased immunity, which provided protection against PrV infection.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…However, the short half-lives of recombinant cytokines and the side effects caused by repetitive administration are major disadvantages for their use (39). Previous reports showed that the direct injection of cytokine genes into muscles might modulate immune responses (18,40,41). Here, we report a eukaryotic expression plasmid carrying ChIL-18 in order to investigate its immunogenic potential as a genetic adjuvant for inducing immune responses in chickens.…”
Section: Discussionmentioning
confidence: 99%